Induction of systemic resistance in cucumber plants against powdery mildew under field conditions - Mohamed, Gehad M.; Ismail, Marawa M. (2016)
Cucumber (Cucumis sativus L.) plants are liable to infect by many fungal pathogens. However, powdery mildew caused by Erysiphe cichoracearum and Sphaerotheca iUliginea, is a very damaging. Foliar application of cucumber plants cv. Beit Alpha with the fungicide thiophanate- methyl (Topsin 70% WP) as a comparison treatment, potassium silicate (5 m/l), dry yeast (4000 mg/l) and ascorbic acid (100 mg/l), significantly reduced disease severity by 86.00, 68.31, 50.86 and 42.03%, respectively compared with the untreated plants in 2013 season. The same trend was found in 2014 season (86.02, 71.33, 48.06 and 45.27%), respectively. Moreover, the aforementioned treatments significantly increased each of plant height/plant, number of leaves/plant, dry weight/plant and number of flowers as well as yield components (number of fruits/plant and mean of fruits weight/plant). Also, the treatments increased peroxidase activity and total phenolic content. Reduction in disease severity was positively correlated with both of peroxidase activity (R2 = 56.3, P < 0.005) and total phenolic content (R2 = 77.2, P < 0.005). Foliar application with potassium silicate, dry yeast and ascorbic acid at the rate of 5ml, 4000 mg and 100 mg/1 induced new pathogenesis related proteins (PR-protein) with various molecular weights in the shoots of cucumber plants upon natural infection with the powdery mildew pathogen. Furthermore, these treatments resulted in a significant increase of N, P, K contents of vegetative shoots. Key words: Cucumber, powdery mildew, foliar spray, induced systemic resistance, peroxidase activity, total phenolic content, pathogenesis-related protein.
Includes references.
Summary in Arabic.
1
Keywords: Cucumbers -- Diseases and pests; Powdery mildew diseases; Plant regulators -- Foliar application